2023
DOI: 10.1186/s12887-023-03854-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between vitamin D level in mother’s serum and the level of vitamin D in the serum of pre-term infants

Abstract: Background Vitamin D deficiency and insufficiency is common in mothers and infants. The present study was conducted with the aim of association between the level of vitamin D in the mother’s serum and the level of vitamin D in the serum of preterm infants. Method The present descriptive – analytical study was performed on 140 mothers and preterm infants referred to the Kamali hospital in Alborz University of Medical Sciences. Sampling was done from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In our study, newborns' serum vitamin D levels in both the opioid and non-opioid groups participating were found to be deficient (< 20 ng/ml) (25). This finding was attributed to inadequate nutrition and lack of vitamin D supplementation due to poor prenatal care, preterm birth, and low socioeconomic status associated with unemployment.…”
Section: Discussionmentioning
confidence: 54%
“…In our study, newborns' serum vitamin D levels in both the opioid and non-opioid groups participating were found to be deficient (< 20 ng/ml) (25). This finding was attributed to inadequate nutrition and lack of vitamin D supplementation due to poor prenatal care, preterm birth, and low socioeconomic status associated with unemployment.…”
Section: Discussionmentioning
confidence: 54%
“…Many studies have demonstrated that low levels of VD during pregnancy can result in low levels of VD in premature infants after they are born. [24][25][26] According to Milan et al, 27 GDM patients had lower serum VD levels and serum VD was negatively correlated with their fasting blood glucose levels. Additionally, higher expression of genes linked to VD resistance was seen in GDM patients, and this expression was inversely correlated with serum VD levels.…”
mentioning
confidence: 99%
“…According to studies, the prevalence of VDD in the general population is very important and pregnancy is one of the known risk factors (RFs) for this deficiency, and in general VDD has been reported between 47 and 83% in black and white pregnant women respectively [16]. Vitamin D status in the fetus and newborn is largely determined by the vitamin D status of the mother [16]. Since VDD is prevalent in mothers, many infants are also at risk of deficiency and insufficiency of vitamin D levels [16].…”
mentioning
confidence: 99%
“…Vitamin D status in the fetus and newborn is largely determined by the vitamin D status of the mother [16]. Since VDD is prevalent in mothers, many infants are also at risk of deficiency and insufficiency of vitamin D levels [16]. Τherefore, when we assume that mothers will suffer much more from VDD, during the corona period, due to theoretically less sun exposure that deteriorate vitamin D synthesis to the skin, with the same rationale we imagine that newborns will suffer the same, due to the quarantine and restrictions on movement from home.…”
mentioning
confidence: 99%